2023
DOI: 10.1371/journal.pone.0288920
|View full text |Cite
|
Sign up to set email alerts
|

Regadenoson for the treatment of COVID-19: A five case clinical series and mouse studies

Abstract: Background Adenosine inhibits the activation of most immune cells and platelets. Selective adenosine A2A receptor (A2AR) agonists such as regadenoson (RA) reduce inflammation in most tissues, including lungs injured by hypoxia, ischemia, transplantation, or sickle cell anemia, principally by suppressing the activation of invariant natural killer T (iNKT) cells. The anti-inflammatory effects of RA are magnified in injured tissues due to induction in immune cells of A2ARs and ecto-enzymes CD39 and CD73 that conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Although the role of A2AR in the severity of SARS-CoV-2 infection has been hypothesized [ 32 , 33 , 34 ] and preliminary clinical data indicate that the infusion of either adenosine or of a selective A2AR agonist may dampen inflammation in COVID-19 patients [ 35 , 36 ], our study did not reveal any association between SARS-CoV-2 infection and the rs2298383 SNP of A2AR, a loss-of-function polymorphism associated with bolstered immune response [ 28 ]. We have previously shown in the context of brain diseases that the altered role of A2AR depends both on the up-regulation of A2AR as well as an increased formation of extracellular adenosine [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the role of A2AR in the severity of SARS-CoV-2 infection has been hypothesized [ 32 , 33 , 34 ] and preliminary clinical data indicate that the infusion of either adenosine or of a selective A2AR agonist may dampen inflammation in COVID-19 patients [ 35 , 36 ], our study did not reveal any association between SARS-CoV-2 infection and the rs2298383 SNP of A2AR, a loss-of-function polymorphism associated with bolstered immune response [ 28 ]. We have previously shown in the context of brain diseases that the altered role of A2AR depends both on the up-regulation of A2AR as well as an increased formation of extracellular adenosine [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown in the context of brain diseases that the altered role of A2AR depends both on the up-regulation of A2AR as well as an increased formation of extracellular adenosine [ 40 , 41 , 42 , 43 ]. Thus, the contrasting evidence that A2AR properties seems unrelated to the severity of COVID-19 whereas exogenously added agonists provide a clinical benefit [ 35 , 36 ] is suggestive that the major modification in the adenosine system associated with COVID-19 might be the availability of extracellular adenosine. Future studies assessing the levels of extracellular adenosine as well as the function of A2AR during infection, or of other SNPs of A2AR [ 27 ], are needed to better understand a possible role of the adenosine A2AR modulation system in SARS-CoV-2 pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, positron emission tomography combined with computed tomographic imaging has shown a positive correlation between calcification and inflammation in the skin and arteries of a 42-year-old PXE patient [159]. At this point in time, the connection between ABCC6 function and IL-6 is not clear, however a recent study could provide some clues [200]. A very recent publication by Casemayo et al showed that Abcc6 deficiency produced an immune modulation with positive effects on the renal manifestations of rhabdomyolysis [158].…”
Section: Immune Cells and Inflammationmentioning
confidence: 97%